Affective commitment as a moderator of the adverse relationships between day-specific self-control demands and psychological well-being - Rivkin, Wladislaw (Elsevier, 2015)
Recent research has focused on the day-specific adverse effects of stressors at work. Thus, in the present study,we examine the relationships between day-specific work-related self-control demands (SCDs) as a stressor and day-specific indicators of psychological well-being(ego depletion, need for recovery, and work engagement). On the basis of the limited strength model of self-control,we predict that SCDs deplete limited regulatory resources and impair psychological well-being. Furthermore, we propose affective commitment as a buffering moderator of this relationship. Consistent with the broaden and build theory of positive emotions and the self-determination theory,we suggest that affective commitment satisfies employees basic psychological needs and provides positive emotions,which,in turn,help restore limited regulatory resources. Thus, affective commitment should buffer the negative relationships between day-specific SCDs and day-specific psychological well-being.To examine our hypotheses,we conducted a diary study with N=60 employees over 10 working days and used multi-level models to test our predictions.Our results demonstrated that day-specific SCDs indeed impaired indicators of psychological well-being. Furthermore, affective commitment buffered these adverse relationships; thus,on days with high SCDs,highly committed employees reported higher levels of psychological well-being than did less committed employees.
PUBLISHED
Keywords: Self-control demands; Organizational commitment; Diary study; Multi-level analysis; Ego depletion; Psychological well-being